2018
DOI: 10.1159/000491699
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Network of Immune, Endocrine and Metabolic Markers is Associated to More Severe Human Chronic Chagas Cardiomyopathy

Abstract: Individuals who are infected with Trypanosoma cruzi develop chronic Chagas cardiomyopathy (CCC), which is a complication involving a series of immune pathogenetic mechanisms, although an association between immune and metabolic alterations was more recently proposed. Accordingly, we investigated the immuno-metabolic response in chagasic patients and their possible influence on CCC pathogenesis. To this end, T. cruzi-seropositive (asymptomatic or with CCC) and sero-negative individuals were studied. Serum tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In this regard, several researchers have shown increased expression of pro-inflammatory cytokines in serum as well as in tissue in different experimental models of Chagas disease (52,53), as well as associations between the increase in their concentration during the acute stage of the disease and the loss of contractile capability of myofibers during the chronic phase (54). Others have shown elevated pro-inflammatory cytokines in serum and heart sections of patients with CCC in comparison with patients with chronic asymptomatic infection (55)(56)(57)(58). Interestingly, SNP polymorphisms in the genes encoding for pro-inflammatory cytokines, are involved in variations in serum concentration of the coded cytokines and might be related to the progression of CCC (59).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several researchers have shown increased expression of pro-inflammatory cytokines in serum as well as in tissue in different experimental models of Chagas disease (52,53), as well as associations between the increase in their concentration during the acute stage of the disease and the loss of contractile capability of myofibers during the chronic phase (54). Others have shown elevated pro-inflammatory cytokines in serum and heart sections of patients with CCC in comparison with patients with chronic asymptomatic infection (55)(56)(57)(58). Interestingly, SNP polymorphisms in the genes encoding for pro-inflammatory cytokines, are involved in variations in serum concentration of the coded cytokines and might be related to the progression of CCC (59).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amount of the experimental evidence indicated that the degree of dissociation between ACTH and GC secretion is of clinical relevance, as it has been associated with the level of complications of sepsis, surgery, malignant disease, and depression. In the context of human Chagas disease, beyond the disturbed HPA response in terms of the CG/dehydroepiandrosterone ratio, GC levels fell within normal levels (57,58). Nevertheless, it is possible that during the acute symptomatic phase of human Chagas disease, as seen in the highly lethal oral acute infection (28,29), the regulation of GC production may be like the one seen in the experimental model.…”
Section: Discussionmentioning
confidence: 97%
“…55 Importantly, IL-6 has been found to be significantly elevated in the serum of CCC patients and experimental animal models of CCC. [56][57][58] IL-6 is a pleiotropic cytokine that can induce both inflammatory and fibrotic pathways through STAT3 signalling. 59 Chronic activation of STAT3 in the heart has been demonstrated to cause excessive inflammation, ventricular rupture and death.…”
Section: Discussionmentioning
confidence: 99%